Hindbrain Estrogen Receptor Regulation of Ventromedial Hypothalamic Glycogen Metabolism and Glucoregulatory Transmitter Expression in the Hypoglycemic Male Rat - Ali, Md. Haider (Neuroscience, 2019)
Estrogen receptor-alpha (ERα) and -beta (ERβ) occur in key elements of the brain gluco-homeostatic network in both sexes, including the hindbrain dorsal vagal complex (DVC), but the influence of distinct receptor populations on this critical function is unclear. The ventromedial hypothalamic nucleus (VMN) maintains glucose balance by integrating nutrient, endocrine, and neurochemical cues, including metabolic sensory information supplied by DVC A2 noradrenergic neurons. Current research utilized the selective ERα and ERβ antagonists MPP and PHTPP to characterize effects of DVC ERs on VMN norepinephrine (NE) activity and metabolic neurotransmitter signaling in insulin-induced hypoglycemic (IIH) male rats. Data show that ERβ inhibits VMN glycogen synthase and stimulates phosphorylase protein expression, while attenuating hypoglycemic augmentation of glycogen content. Furthermore, both ERs attenuate VMN glucose concentrations during IIH. Hypoglycemic up-regulation of nitric oxide (NO) and brain-derived neurotrophic factor (BDNF) signaling was correspondingly driven by ERα or -β, whereas GABA and steroidogenic factor-1 were respectively suppressed independently of ER input or by ERβ. IIH intensified VMN NE accumulation by ERβ-dependent mechanisms, but did not alter NE levels in other gluco-regulatory loci. ERβ amplified the magnitude of insulin-induced decline in blood glucose. Both ER regulate corticosterone, but not glucagon secretion during IIH and oppose hypoglycemic diminution of circulating free fatty acids. These findings identify distinguishing versus common VMN functions targeted by DVC ERα and -β. Sex differences in hypoglycemic VMN NE accumulation, glycogen metabolism, and transmitter signaling may involve, in part, discrepant regulatory involvement or differential magnitude of impact of these hindbrain ERs.